Xiang yuan (village worthies) : the appearance-only hypocrite - Sung, Winnie (2020)
This article seeks to interpret Mencius’ criticism of the village worthies (xiang yuan 鄉原) and shed light on the distinctive psychological phenomenon that Mencius has captured but not quite articulated. An attempt at filling out the Mencian view of the village worthies will help us better understand the content of the moral charges made against them and also deepen our analysis of the kind of psychology that early Confucians regard as crucial to moral agency. Following an introduction that overviews Mencius’ criticisms of the village worthies, the main discussion of this article is divided into three sections. Section 2 offers an interpretation of the psychology of the village worthy and articulates the way in which the village worthy can be regarded as a special kind of hypocrite, which I label as “appearance-only” hypocrite. Section 3 draws on the proposed interpretation to make sense of Mencius’ criticisms of the village worthy. I argue that while the village worthy can elude some common charges against hypocrisy, it is still problematic in the sense that it weakens an unstable system of morality from the inside and inflicts harm on the genuinely virtuous person. Section 4 delves deeper into analyzing the ethical implications for the self and for others.